ANALYSIS OF THE INFLUENCE OF ENVIRONMENTAL PERFORMANCE AND CORPORATE SOCIAL RESPONSIBILITY (CSR) ON FINANCIAL PERFORMANCE IN SRI-KEHATI INDEX COMPANIES - Gita Afrillia; Juli Meliza (Jurnal Ekonomi, 2023)
Study This aim For know and analyze How influence performance environment and CSR towards performance company finance _ SRI KEHATI Index . Source of data used in study This report finances and reports PROPER assessment published by the Ministry of Environment Life through the website www.menlh.go.id . Method data analysis used in study This is descriptive quantitative . Study This done based on the data obtained during period 2009 to 2018. In study This writer count ratio with use Return On Assets (ROA) and Corporate Social Responsibility . Research results This show that performance environment and CSR towards performance finance experience not optimal and experienced fluctuation during 10 year period to lower matter This seen Because a number of company that doesn't fulfil the conditions inside regulation of the Minister of the Environment live